Upaya Meningkatkan Nilai-Nilai Karakter Peserta Didik Melalui Penerapan Metode Role-Playing: Indonesia - Nursalim; Elsunarti (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2019)
This study aims to determine the implementation of role-playing to increase the character values ​​of students in Citizenship Education learning. This research is classroom action research. This action research was carried out in the even semester of 2018/2019 for the subject of Citizenship Education for grade 3 students of SD Negeri 37 Pekanbaru. Data collection techniques used were observation, interviews, and documentation. The stages of this research are the planning stage, action implementation, monitoring and evaluation, analysis, and reflection. The results of this study indicate an increase in student character values ​​which can be seen from the indicators of discipline, hard work, creativity, and student communication skills. The biggest increase occurred in creative value (19.6%), in communication skills there was an increase of 18.9%. In the discipline indicator, there was an increase of 10.9%. The hard work indicator was still at the bottom of the increase in each character indicator, which only showed an increase of 7.4%.